Predicción del Proceso de Inyección de Agua Mediante Simulación Analítica: Sector Norte del Campo Lisama, Formación Mugrosa, Método Craig Geffen & Morse (2010)
Lisama Field is located at Middle Magdalena Valley Basin and operated by ECOPETROL S.A, produce mainly from Colorado and Mugrosa formations. After developed a technical-experimental feasibility study, waterflooding resulted as a proper method to implement in this field. For instance, it realized prediction through analytical simulation for determine profitable on the development of this process.